Petrographic and geochemical studies for depositional and diagenetic modelling of Miocene Sibuti Formation, NW Borneo: Implications on reservoir characterization, tectonic and sea level dynamics - Tan, Samantha Wei Ling (Curtin University, 2024)
NO ABSTRACT